An ATG16L1-dependent pathway promotes plasma membrane repair and limits Listeria monocytogenes cell-to-cell spread. (December 2018) - Tan, Joel; Mellouk, Nora; Osborne, Suzanne; Ammendolia, Dustin; Dyer, Diana; Li, Ren; Brunen, Diede; Rijn, Jorik; Huang, Ju; Czuczman, Mark; Cemma, Marija; Won, Amy; et al.
Abstract Plasma membrane integrity is essential for the viability of eukaryotic cells. In response to bacterial pore-forming toxins, disrupted regions of the membrane are rapidly repaired. However, the pathways that mediate plasma membrane repair are unclear. Here we show that autophagy-related (ATG) protein ATG16L1 and its binding partners ATG5 and ATG12 are required for plasma membrane repair through a pathway independent of macroautophagy. ATG16L1 is required for lysosome fusion with the plasma membrane and blebbing responses that promote membrane repair. ATG16L1 deficiency causes accumulation of cholesterol in lysosomes that contributes to defective membrane repair. Cell-to-cell spread byListeria monocytogenes requires membrane damage by the bacterial toxin listeriolysin O, which is restricted by ATG16L1-dependent membrane repair. Cells harbouring the ATG16L1 T300A allele associated with inflammatory bowel disease were also found to accumulate cholesterol and be defective in repair, linking a common inflammatory disease to plasma membrane integrity. Thus, plasma membrane repair could be an important therapeutic target for the treatment of bacterial infections and inflammatory disorders. Autophagy-related proteins ATG16L1, ATG5 and ATG12 are required for plasma membrane repair and help to restrictListeria monocytogenes toxin-mediated cell-to-cell spread.